Austeridade fiscal na periferia da Zona do Euro: análise comparativa entre Grécia e Portugal - Pedro Vitor Garcia Ramos (2021)
Different concepts about the real economy can generate distinct conclusions about the application of economic policies. Grounded in schools of thought that seek answers to economic depressions using anti-cycled measures is possible to infer that fiscal consolidation, in a recessive environment, is a misconception. Events categorized as fiscal austerity are the main study objects of this work, especially those presented after the 2008 crisis as correctors of peripherical countries, in Europe, debts. Among those, Greece and Portugal have been highlights in the actual conjuncture during the application of plan proposal by the European Central Bank, International Monetary Fund, and the European Commission (Troika). From the Greek side is possible to observe the creation and maintenance of an economic crisis that its deeper root does not allow a rapid recovery, on the Portuguese side, the disruption with the application of austerity plans and reverse of measures, done during Pedro Passos’ government, indicates a fruitful way with good samples of economic recovery. One of the main questions this study seeks to answer is: what elements are responsible for the trajectory’s differentiation taken by both countries? Three of the main factors can be named: (i) the difference of maintenance, in years, of the applied plans; (ii) the severity and reinforcement of the measures in Greece; (iii) the reversal of measures done by Costa’s government in Portugal. A couple of elements, also explored in the lines that follow, are crucial for understanding the crisis. First is the lack of a mechanism to compensate for the inner disbalance that outcomes from commerce in the Euro Area. This is shown as the originator of a structural and persistent crisis, where the peripheral countries’ public debt presents deterioration fronts the central nations. The second is the inner characteristic in the rescue programs done by Troika in these territories and how this affects the income growth. The highest number of measures was implemented from the expense side, where the fiscal multiplier, related to the revenue (in both countries), turned out to be bigger. From a statistical point of view, these multipliers were calculated utilizing the autoregressive vectors (VAR) methodology, although none with characteristics capable of corroborating the expansionary austerity idea. The cuts of public debt had a recessive character and a higher relevance than the increase in revenue. Uniting a theory-critical part, a descriptive one, and, in the end, a statical one, it’s plainness that the situation in Greece could have been avoided and the austerity plans were the main responsible for the generation and perpetuation of a humanitarian crisis on Greek soil.